2017
DOI: 10.1007/s11433-017-9086-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field annihilation and reconnection driven by femtosecond lasers in inhomogeneous plasma

Abstract: The process of fast magnetic reconnection driven by intense ultra-short laser pulses in underdense plasma is investigated by particle-in-cell simulations. In the wakefield of such laser pulses, quasi-static magnetic fields at a few mega-Gauss are generated due to nonvanishing cross product ∆(n /γ) × p. Excited in an inhomogeneous plasma of decreasing density, the quasi-static magnetic field structure is shown to drift quickly both in lateral and longitudinal directions. When two parallel-propagating laser puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…It was demonstrated that the magnetic field damping in the non-relativistic case is at least three times longer, and the electric fields coming from the displacement current term in Ampere’s law are negligible, see Wang et al. (2016).…”
Section: Pic Simulation Results and Theoretical Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the magnetic field damping in the non-relativistic case is at least three times longer, and the electric fields coming from the displacement current term in Ampere’s law are negligible, see Wang et al. (2016).…”
Section: Pic Simulation Results and Theoretical Estimatesmentioning
confidence: 99%
“…2016; Wang et al. 2016). In the case of our simulations, the ratio of the term to the current term with the increased density can be written as (by an order of magnitude): , where accounts for possible increase of the current due to the increase in electron density with in our simulations.…”
Section: Pic Simulation Results and Theoretical Estimatesmentioning
confidence: 99%
“…In the cases of astrophysical and laboratory plasmas, the magnetic reconnection plays a key role in a broad range of processes exemplified by solar flares [6][7][8], coronal mass ejections [9,10], open and closed planetary magnetospheres [11][12][13], gamma-ray bursts [14][15][16][17] and nuclear fusion plasma instabilities [18][19][20][21]. Due to the recent progress in laser technology, high power lasers were employed to study the fast magnetic reconnection regime [22][23][24][25][26][27]. In fact, when a high-intensity laser pulse interacts with a plasma target the accelerated electron bunches generate strong magnetic fields with non-trivial topology.…”
Section: Introductionmentioning
confidence: 99%